THE INFLUENCE OF THE AUDIT COMMITTEE AND FRAUD DIAMOND ON FRAUDULENT FINANCIAL STATEMENT IN MANUFACTURING COMPANIES OF VARIOUS INDUSTRIES SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Suripto - Suripto; Karmilah Karmilah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Fraudulend financial statement are generally difficult to detect, due to the various motivations behind the actions taken. The purpose of this study is to prove the effect of the audit committee and the fraud diamond on the fraudulent financial statement by looking at the effect of the variables that are proxies in this study. The population in this study were manufacturing companies in the various industrial sectors in 2015-2019. The sampling technique in this research is purposive sampling. The type of data used is secondary data from the Indonesia Stock Exchange in the form of an annual report. The sample in this study were 22 companies, with 110 observational data. The type of research method used is panel data regression analysis method. The results of the analysis of this study indicate that simultaneously the audit committee and the fraud command element have an effect on the fraudulent financial statement and partially show that only financial stability and financial targets have an effect on the fraudulent financial statement. While the financial target variables, nature of industry, ineffective monitoring, change in auditors, change of directors and audit committees have no effect on fraudulent financial statement. Keywords: Audit Committee, Fraud Diamond, Fraudulent Financial Statements, Manufacturing Companies of Various Industries Sector